Fast-Track in Minimally Invasive Gynecology: A Randomized Trial Comparing Costs and Clinical Outcomes - Lambat Emery, Shahzia; Brossard, Philippe; Petignat, Patrick; Boulvain, Michel; Pluchino, Nicola; Dällenbach, Patrick; Wenger, Jean-Marie; Savoldelli, Georges L.; Rehberg-Klug, Benno; Dubuisson, Jean (Frontiers in Surgery, 2021)
Study objective: Evaluate the effects of a fast-track (FT) protocol on costs and postoperative recovery. Methods: 170 women undergoing total laparoscopic hysterectomy for a benign indication were randomized in an FT protocol or a usual care protocol. A FT protocol included the combination of minimally invasive surgery, analgesia optimization, early oral refeeding and rapid mobilization of patients was compared to a usual care protocol. Primary outcome was costs. Secondary outcomes were length of stay, postoperative morbidity and patient satisfaction. Main results: The mean total cost in the FT group was 13,070 ± 4,321 Euros (EUR) per patient, and that in the usual care group was 3.5% higher at 13,527 ± 3,925 EUR (p=0.49). The FT group had lower inpatient surgical costs but higher total ambulatory costs during the first postoperative month. The mean hospital stay in the FT group was 52.7 ± 26.8 hours, and that in the usual care group was 20% higher at 65.8 ± 33.7 hours (p=0.006). Morbidity during the first postoperative month was not significantly different between the two groups. On their day of discharge, the proportion of patients satisfied with pain management was similar in both groups (83% in FT and 78% in the usual care group (p=0.57)). Satisfaction with medical follow-up one month after surgery was also similar (91% in FT and 88% in the usual care group (p=0.69)). Conclusion: Implementation of a FT protocol in laparoscopic hysterectomy for benign indications has minimal non-significant effects on costs but significantly reduces hospital stay without increasing postoperative morbidity nor decreasing patient satisfaction.